The Effect of Teacher Creativity On Student Learning Interest of The Seventh Grade Students at Junior High School 2 Parepare - Nun Afifa; Patahuddin; Amir Patintingan (La Parole : Journal of Language Teaching and Pedagogy, 2019)
This research was conducted to know how the teachers effect on their students. In particular, the influence of teacher creativity on students' interest in learning in seventh grade SMP Negeri 2 Parepare. Teacher creativity is one way to increase student interest in learning, therefore researchers researched to determine how efficiently the influence of teachers on students in seventh grade of Junior High School 2 Parepare. This type of research is a qualitative one conducted with teachers and students. The population of this research is the seventh grade of junior high school 2 Parepare. The respondents of this study consisted of 3 seventh grade teachers. Researchers conducted interview and observation to obtain data. The results showed that the teacher's creativity in teaching greatly increased student interest in learning. Students become very enthusiastic and excited about the teaching and learning process. Especially in this modern era, teaching millennial children is very difficult; therefore it requires high teacher creativity.